Kombinasi Ekstrak Etanol 96% Daun Teh (Camellia sinensis (L.) Kuntze) dan Daun Yakon (Smallanthus sonchifolius) sebagai Penghambat Enzim ?-glukosidase: Combination of 96% Ethanol Extract of Tea Leaves (Camellia sinensis Linn.) and Yakon Leaves (Smallanthus sonchifolius) as an Inhibitor of the ?-glucosidase enzyme - Lilik Sulastri; Rohmat Hidayat; Padmono Citroreksoko; Syamsudin Abdillah; Partomuan Simanjuntak (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Diabetes mellitus is a degenerative disease in the form of metabolic disorders characterized by increased blood glucose levels and impaired insulin metabolism. Yakon leaves and tea leaves contain phenolic compounds which have ?-glucosidase inhibiting activity. The aims of this study was to determine the inhibitory activity of the ?-glucosidase enzyme from tea leaf and yakon leaf extracts and the combination of the two plants. Extraction of the active compounds contained in tea leaves and yakon leaves was carried out by graded maceration method using n-hexane, ethyl acetate, 96% ethanol and water as solvents (using the decoction method). Phytochemical analysis of 96% ethanol extract of tea leaves and yakon leaves contained alkaloids, flavonoids, tannins, saponins, triterpenoids/steroids and phenols. The results of testing the inhibitory activity of the -glucosidase enzyme showed that the IC50 values ??for 96% ethanol extract of tea leaves and yakon leaves were 22.31 and 19.70 ppm, respectively. Combination of 96% ethanol extract of tea leaves and yakon leaves in a ratio of 1:1; 1:3; 3:1 obtained IC50 of 64.73 ppm respectively; 7.34 ppm, and 11.03 ppm.